A grammar of Hyow - Muhammad Zakaria (2018)
Hyow is an undocumented language, with about four thousand speakers living in the southeast of Bangladesh. This dissertation describes the linguistic features of this undocumented language. This dissertation consists of twelve chapters, a text, a Hyow-English dictionary, three appendices and references. The first chapter of this grammar contains an introductory discussion of the land, life and language of Hyow. An attempt has been made to work out the genetic relation of Hyow with other Kuki-Chin languages in this chapter. The second chapter includes the description of phonetics and phonology, which addresses the vowel and consonant inventory, phonotactics, acoustic analysis, phonological processes and tone sandhi among other topics. The third chapter deals with the word classes found in Hyow. Different formal properties have been used to identify the open and closed word classes in this chapter. The fourth and the fifth chapter are dedicated to a discussion of noun phrase constituents and morphology of nominals, and also address word formation processes. Verbs play an important role in the grammar of Hyow. The sixth chapter focuses on stem alternations and various classes of verbs. The seventh, eighth and ninth chapters concentrate on the morphology of verbs. The tenth chapter includes discussion on grammatical functions and argument indexation on verbs. Case-marking morphology and argument indexation have been utilized to identify the grammatical functions in this chapter. Other than the morphosyntactic coding of core arguments, markings of oblique arguments have also been made in this chapter. Finally, the eleventh and the twelfth chapters deal with structures of simple clauses and complex sentences respectively. The discussion of complex sentences includes adverbial, relative and complement clauses. In addition, discussions have been also done on relative-correlative and comparative-correlative constructions. One text from the corpus has been added as a sample. There is also a bilingual dictionary of about three thousand and one hundred words. The appendices include tokens of acoustic analysis, permitted inflectional categories to the dependent and imperative verbs. At the end of this grammar, a list of references have been given. This is the first attempt of writing a grammar of the language. Out of many interesting linguistic features of Hyow, tone sandhi, verb stem variants and their functions, person hierarchy, middle voice, clausal nominalization and strategies of forming complex clauses are noteworthy. The findings of tone sandhi in Hyow will contribute to understand tone patterns of other undocumented Southern Chin languages. The discussion on stem variants based on their uses in different types of clauses will add to the study of stem alternations in Kuki-Chin languages. The effect of stem alternations on lexical tones might be useful for further study of tonal correspondences among different Kuki-Chin languages. Among the documented Southern Chin languages only Hyow and Asho (Otsuka 2015) show person hierarchy for argument indexations on verbs. This can be useful to determine the lower-level classifications of Kuki-Chin languages. Middle voice plays an important role in the grammar of Hyow. However, this topic has not been widely discussed in other Kuki-Chin languages. The extensive discussion of middle voice in this dissertation will contribute to future studies of middle voice in other Kuki-Chin languages. The use of clausal nominalization again demonstrates how significant it is in Tibeto-Burman languages. To sum up, this dissertation is expected to further the studies of Kuki-Chin languages in the future.